Social justice and charitable-trust in Islamic financial transactions - Adam Sa'ad, Auwal; Ibrahim, Uzaimah (Zes Rokman Resources (2131022-P), 2015)
The Islamic model of Social Justice and Charitable-Trust are the most important concepts which made the Islamic Banking and Finance a unique system with moral, honesty and fair economic setting. The Islamic economic system has recognized individual and public ownerships. It provides certain rules and regulations that restored justice in maintaining the two different types of ownerships without any one’s trespass on another. The paper highlights issues and contracts which are based on trust and charity wise arrangement. Murabahah transaction has been the forefront of trust contracts in promoting charitable financial transactions. The paper highlights different types of Murabahah transactions. It also highlights Issues related to benevolent debt (Qardh Alhasan)and its role in balancing the economic system of the Muslim society. The paper concluded that the Islamic economic policies are the most just and moderate policies which protected both the rights of poor and the wealthy individuals. It also minimizes the huge gabs between prosperous and low income individuals.